Ensuring Responsible Nanotechnology Innovation - Jianni Tien; Katherine Kenny; Alex Broom; Alice Motion; Stephen Bartlett (NanoEthics)
Abstract The challenge of considering the ethical, environmental, economic, social, legal and cultural (E3LSC) dimensions of nanotechnology innovation is of enduring and increasing importance for societies worldwide. This is made more pressing due to rising public interest in the realms of AI and quantum technology. Drawing on an interdisciplinary collaboration between nanotechnology and social science researchers, this paper discusses how E3LSC dimensions are negotiated in practice and what lessons can be brought forward to develop E3LSC considerations as nanotechnology and nanoscience continue to advance. Drawing on sociological data from 34 semi-structured interviews with academic scientists researching nanotechnology in Australia, we discuss the contemporary challenges facing nanotechnology researchers. These included acknowledgement of the complexities of navigating E3LSC within the realities of the contemporary university landscape; the increasing turn toward commercialisation in Australia, and the enduring challenges of multidisciplinarity. We discuss how these challenges are complex, but suggest that effective embedding of disciplinary training can contribute to ‘upstreaming’ E3LSC considerations for the betterment of nanotechnology innovation and society alike.